A numerical study of turbulent flow through a variable area orifice meter. (4th August 2014) - Mokhtarzadeh–Dehghan, M.R.; Yu, L.; Stephens, D.J.
The paper describes a numerical study of turbulent flow through an orifice plate restricted by an obstruction of conical shape at its centre. Such a situation occurs in flow metering devices which work on the principle of variable flow area rather than fixed area, as in simple orifice plate meters. The governing differential equations of continuity and momentum and the equations for the k–ε model of turbulence are solved using a finite element method. The velocity and pressure fields and the variation of pressure along the pipe wall are presented. The results show a significant rise in the irrecoverable pressure loss which may reduce the advantage of the meter over simple orifice meters in practice. For comparison, the flow field for a simple orifice plate of the same overall geometry has also been presented. The discharge coefficient for this latter case has been predicted with an error of about 1%, compared with published empirical data.